Konstruksi Naratif Mahasiswa melalui Parafrase Poster dalam Analisis Keterampilan Menulis Cerpen Berbasis Transformasi Multimodal - Sugianti Sugianti; Ilmiyatur Rosidah (Adjektiva: Educational Languages and Literature Studies, 2026)
This study aims to describe the process of students' narrative construction in the Indonesian Language and Literature Education Study Program (PBSI) at Universitas PGRI Wiranegara (Uniwara) through poster paraphrasing activities as a trigger for writing short stories. This research is grounded in the observation that students still show limited imagination in the creative writing process, so a visual medium capable of stimulating ideas and creativity is needed. Posters were chosen as the triggering material because they contain visual, verbal, and typographic elements that can be transformed into narrative texts through a cross-modal paraphrasing process. This study employed a descriptive qualitative approach involving 8 karya PBSI Uniwara students as subjects. Data were collected through students' short-story writings, observation of the writing process, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings show that poster paraphrasing activities improved students' ability to develop ideas, construct plots, build characters, and enrich story settings through a multimodal transformation from the visual mode to the verbal mode. This study contributes to the development of visual-media-based creative writing strategies in higher education.